Seasonal Changes in Photoperiod: Effects on Growth and Redox Signaling Patterns in Atlantic Salmon Postsmolts - Peng Yin; Takaya Saito; Per Gunnar Fjelldal; Björn Thrandur Björnsson; Sofie Charlotte Remø; Tom Johnny Hansen; Sandeep Sharma; Rolf Erik Olsen; Kristin Hamre (MDPI AG, 2023)
Farmed Atlantic salmon reared under natural seasonal changes in sea-cages had an elevated consumption of antioxidants during spring. It is, however, unclear if this response was caused by the increase in day length, temperature, or both. The present study examined redox processes in Atlantic salmon that were reared in indoor tanks at constant temperature (9 °C) under a simulated natural photoperiod. The experiment lasted for 6 months, from vernal to autumnal equinoxes, with the associated increase and subsequent decrease in day length. We found that intracellular antioxidants were depleted, and there was an increase in malondialdehyde (MDA) levels in the liver and muscle of Atlantic salmon with increasing day length. Antioxidant enzyme activity in liver and muscle and their related gene profiles was also affected, with a distinct upregulation of genes involved in maintaining redox homeostasis, such as peroxiredoxins in the brain in April. This study also revealed a nuclear factor-erythroid 2-related factor 2 (Nrf2)-mediated oxidative stress response in muscle and liver, suggesting that fish integrate environmental signals through redox signaling pathways. Furthermore, growth and expression profiles implicated in growth hormone (GH) signaling and cell cycle regulation coincided with stress patterns. The results demonstrate that a change in photoperiod without the concomitant increase in temperature is sufficient to stimulate growth and change the tissue oxidative state in Atlantic salmon during spring and early summer. These findings provide new insights into redox regulation mechanisms underlying the response to the changing photoperiod, and highlight a link between oxidative status and physiological function.